Mangkoan Sound: the Concept of Traditional Talempong Prohibition in Luhak nan Tigo Minangkabau - Martis Martis; Yunaidi Yunaidi; Andar Indra Sastra; Syahri Anton; Nurwani Nurwani (Gondang: Jurnal Seni dan Budaya, 2024)
Aesthetically, the aim of this research is to reveal the musical taste and musical standards of tuo talempong in alignment talempong tradition – mangkoan sound. By ontology and epistemology; form music talempong in life public Already Lots revealed by the researchers previously. However there are one component important that hasn't been touched by researchers, which is related to draft alignment talempong tradition in Luhak Nan Tigo Minangkabau. Principle base alignment talempong related with the musical taste and musical standards of the tuo (elders) of talempong in Luhak Nan Tigo Minangkabau. Based on qualitative research principles; The researcher becomes the main instrument in collecting research data,includinginitial study and problem analysis, primary data collection through participant observers – ethnography, in-depth interviews – free and structured, documentation, and data analysis.The analysis was carried out on musical taste and musical standards that were found in the field. Research results show that ' mangkoan the sound ' is A draft alignment talempong tradition in Luhak Nan Tigo Minangkabau. hrough musical sensitivity, tuo talempong in Luhak Nan Tigo Minangkabau created the concept of mangkoan sounds (tala - tuning system) to identify the high and low sounds of jantan-batino talempong.